Thailand’s Anti-Trafficking in Persons Act B.E. 2551 (2008): A New Development in Human Rights Protection and Justice (In Factis Pax: Journal of Peace Education and Social Justice, 2008)
In response to the problem of trafficking in persons, the twin tasks are to protect including prevent the victims and to punish the perpetrators. Both require critical transdisciplinary framework; the first with respect to the principle of human rights, the second with respect to the norm of law. Thailand’s previous 1997 anti-trafficking law is counter productive. Concerted efforts have been advocated to the promulgation of Anti-Trafficking in Persons Act 2008. This comparative study between the two laws will focus on new developments in human rights protection of victims and bringing justice to them in four main areas; 1. Definition, 2. Measures on protection of human rights of victims, 3. Mechanisms for implementation, and 4. Penalties.